Nonhypertensive White Matter Hyperintensities in Stroke: Risk Factors, Neuroimaging Characteristics, and Prognosis - Jae‐Sung Lim; Keon‐Joo Lee; Beom Joon Kim; Wi‐Sun Ryu; Jinyong Chung; Dong‐Seok Gwak; Ji Sung Lee; Seong‐Eun Kim; Eunvin Ko; Juneyoung Lee; Moon‐Ku Han; Eric E. Smith; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background This study explored the risk factors, neuroimaging features, and prognostic implications of nonhypertensive white matter hyperintensity (WMH) in patients with acute ischemic stroke and transient ischemic attack. Methods and Results We included 2283 patients with hypertension and 1003 without from a pool of 10 602. Associations of moderate‐to‐severe WMH with known risk factors, functional outcome, and a composite of recurrent stroke, myocardial infarction, and all‐cause mortality were evaluated. A subset of 351 patients without hypertension and age‐ and sex‐matched pairs with hypertension and moderate‐to‐severe WMH was created for a detailed topographic examination of WMH, lacunes, and microbleeds. Approximately 35% of patients without hypertension and 65% of patients with hypertensive stroke exhibited moderate‐to‐severe WMH. WMH was associated with age, female sex, and previous stroke, irrespective of hypertension. In patients without hypertension, WMH was associated with initial systolic blood pressure and was more common in the anterior temporal region. In patients with hypertension, WMH was associated with small vessel occlusion as a stroke mechanism and was more frequent in the periventricular region near the posterior horn of the lateral ventricle. The higher prevalence of occipital microbleeds in patients without hypertension and deep subcortical lacunes in patients with hypertension were also observed. Associations of moderate‐to‐severe WMH with 3‐month functional outcome and 1‐year cumulative incidence of the composite outcome were significant (both P<0.01), although the latter lost significance after adjustments. The associations between WMH and outcomes were consistent across hypertensive status. Conclusions One‐third of patients without hypertension with stroke have moderate‐to‐severe WMH. The pathogenesis of WMH may differ between patients without and with hypertension, but its impact on outcome appears similar.